Computational Investigation and Experimental Validation of Crizotinib Resistance Conferred by C1156Y Mutant Anaplastic Lymphoma Kinase. Issue 2 (30th January 2015) - Kumar, Anish; Shanthi, V.; Ramanathan, K.
Abstract: Crizotinib is an anticancer drug approved by FDA for the treatment of non‐small cell lung cancer (NSCLC). The main target for crizotinib was anaplastic lymphoma kinase (ALK). However, evidences available indicate that C1156Y mutation in ALK confers resistance to crizotinib. Unfortunately, how mutation actually confers drug resistance is not well understood. Hence, in the present study computational approaches have been employed alongside KINOMEscan profiling technique to reveal the mechanism behind crizotinib resistance in ALK at a molecular level. The results of our analysis indicate that C1156Y mutation alters the conformation of the ALK binding pocket residues which results in a marked decrease in hydrogen bond interactions between crizotinib and ALK. This indicates that hydrogen bonding was a crucial effector of decreased binding affinity. Interestingly, the docking study also indicates that C1156Y mutation increases the affinity for ATP. Finally, our analysis theoretically suggests that M‐1199 is a key residue responsible for the ALK drug selectivity. We certainly believe that these results may be immense importance for the molecular level understanding of crizotinib resistance pattern and also for designing a potential drug molecule for the treatment of lung cancer in the near future. Abstract :